Man in pain - Unknown (Tufts Archival Research Center, 2018)
Black and red image of two men, one of whom appears to be in pain. Text in the bottom right-hand corner of the image reads: "May 70 A. Smals". This is a scan of one of three duplicate posters in the folder.